Backfire [compact disc, unabridged] - Coulter, Catherine (Coulter, Catherine. FBI thrillers, 2012)
San Francisco Judge Ramsey Hunt, longtime friend to FBI agents Lacey Sherlock and Dillon Savich, is presiding over the trial of Clive and Cindy Cahill, accused in a string of murders, when the proceedings take a radical turn. Federal prosecutor Mickey O'Rourke becomes suddenly tentative, leading Hunt to suspect he's been threatened, and when Hunt is shot in the back this is all but confirmed. Now Savich and Sherlock race to San Francisco to investigate, watching their backs all the while.